Maternal knowledge of the maternal and child health handbook and nutritional status among children aged 6–59 months - Syifa Syahirah Azahra; Astri Pinilih; Debi Arivo; Nina Herlina (JOURNAL OF Medical Surgical Concerns, 2026)
Background: The Maternal and Child Health (MCH) Handbook is an integrated home-based record and health-education resource that supports child growth monitoring, nutrition, immunization, feeding practices, and early recognition of health problems. Maternal understanding of the handbook may influence how effectively its information is applied in daily childcare. Purpose: To examine the association between maternal knowledge of the MCH Handbook and the nutritional status of children aged 6–59 months at Rajabasa Indah Public Health Center, Bandar Lampung. Method: This cross-sectional analytic study included 100 mother–child pairs recruited through convenience sampling in 2026. Maternal knowledge was assessed using a questionnaire, and child nutritional status was determined from anthropometric measurements using the weight-for-length/height indicator. Descriptive statistics summarized the study variables, and the chi-square test assessed the association between maternal knowledge and nutritional status. Results: Good knowledge of the MCH Handbook was reported by 82 mothers (82.0%), while 14 (14.0%) had poor knowledge and 4 (4.0%) had moderate knowledge. Eighty-three children (83.0%) had normal nutritional status, 14 (14.0%) were undernourished, and 3 (3.0%) were overnourished. Maternal knowledge was significantly associated with child nutritional status (p < 0.001). Conclusion: Maternal knowledge of the MCH Handbook was associated with the nutritional status of children aged 6–59 months. Because the study was cross-sectional and several contingency-table cells were sparse, the findings indicate an association rather than a causal effect.